Pharmacokinetic Interactions between BMS-626529, the Active Moiety of the HIV-1 Attachment Inhibitor Prodrug BMS-663068, and Ritonavir or Ritonavir-Boosted Atazanavir in Healthy Subjects - Zhu, Li (Antimicrob Agents Chemother, 2015)
BMS-663068 is a prodrug of BMS-626529, a first-in-class attachment inhibitor that binds directly to HIV-1 gp120, preventing initial viral attachment and entry into host CD4(+) T cells. This open-label, multiple-dose, four-sequence, crossover study addressed potential two-way drug-drug interactions following coadministration of BMS-663068 (BMS-626529 is a CYP3A4 substrate), atazanavir (ATV), and ritonavir (RTV) (ATV and RTV are CYP3A4 inhibitors). Thirty-six healthy subjects were randomized 1:1:1:1 to receive one of four treatment sequences with three consecutive treatments: BMS-663068 at 600 mg twice daily (BID), BMS-663068 at 600 mg BID plus RTV at 100 mg once daily (QD), ATV at 300 mg QD plus RTV at 100 mg QD (RTV-boosted ATV [ATV/r]), or BMS-663068 at 600 mg BID plus ATV at 300 mg QD plus RTV at 100 mg QD. Compared with the results obtained by administration of BMS-663068 alone, coadministration of BMS-663068 with ATV/r increased the BMS-626529 maximum concentration in plasma (C(max)) and the area under the concentration-time curve in one dosing interval (AUC(tau)) by 68% and 54%, respectively. Similarly, coadministration of BMS-663068 with RTV increased the BMS-626529 C(max) and AUC(tau) by 53% and 45%, respectively. Compared with the results obtained by administration of ATV/r alone, ATV and RTV systemic exposures remained similar following coadministration of BMS-663068 with ATV/r. BMS-663068 was generally well tolerated, and there were no adverse events (AEs) leading to discontinuation, serious AEs, or deaths. Moderate increases in BMS-626529 systemic exposure were observed following coadministration of BMS-663068 with ATV/r or RTV. However, the addition of ATV to BMS-663068 plus RTV did not further increase BMS-626529 systemic exposure. ATV and RTV exposures remained similar following coadministration of BMS-663068 with either ATV/r or RTV. BMS-663068 was generally well tolerated alone or in combination with either RTV or ATV/r.